2022
DOI: 10.1002/prca.202200062
|View full text |Cite
|
Sign up to set email alerts
|

A protein microarray‐based serum proteomic investigation reveals distinct autoantibody signature in colorectal cancer

Abstract: Purpose Colorectal cancer (CRC) has been reported as the second leading cause of cancer death worldwide. The 5‐year annual survival is around 50%, mainly due to late diagnosis, striking necessity for early detection. This study aims to identify autoantibody in patients’ sera for early screening of cancer. Experimental Design The study used a high‐density human proteome array with approximately 17,000 recombinant proteins. Screening of sera from healthy individuals, CRC from Indian origin, and CRC from middle‐e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…The increasing burden of CAC needs multimodal, non-invasive, and severe assessment of the disease using biochemical, molecular, cellular, and high-throughput systems biology approaches. Early detection and management of CAC need a more in-depth review of the condition with highly sensitive and accurate molecular markers that could serve as an essential tool in screening, diagnosis, and prognosis of CAC. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing burden of CAC needs multimodal, non-invasive, and severe assessment of the disease using biochemical, molecular, cellular, and high-throughput systems biology approaches. Early detection and management of CAC need a more in-depth review of the condition with highly sensitive and accurate molecular markers that could serve as an essential tool in screening, diagnosis, and prognosis of CAC. , …”
Section: Introductionmentioning
confidence: 99%
“…Early detection and management of CAC need a more in-depth review of the condition with highly sensitive and accurate molecular markers that could serve as an essential tool in screening, diagnosis, and prognosis of CAC. 10,11 Recent studies have shown multiple genomic and proteomic alterations, including the de novo lipogenesis (DNL) pathway, revealing the heterogeneous nature of the disease at the molecular level. 9,12 Our previous deep proteomics of CAC has also identified the DNL to be dysregulated with the significant upregulation of the critical enzyme fatty acid synthase (FASN).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Orbitrap Fusion Tribrid Mass Spectrometer (Thermo Scientific) coupled to a nanoLC system (Thermo Scientific) was used for PRM experiments . The isolation generated above was imported in the instrument method for PRM and used further for data acquisition.…”
Section: Methodsmentioning
confidence: 99%
“…The MS RAW files from the 2020 MS dataset (PXD020580 and PXD023016), 2021 MS dataset (PXD029300), and blank MS datasets (See section 1 "MS Datasets" in supplement) were converted into Mascot Generic Format (MGF) files using msconvert tool on Galaxy Europe server (usegalaxy.eu). A large microbial protein sequences database was generated using the Uniprot XML Downloader tool within the Galaxy platform [20] to extract sequences for known genera (33,281,528 protein sequences from 72 genera; See section 2 "Protein Sequences Database" in Supplement) and species (242,901 protein sequences from 7 species; See section 2 "Protein Sequences Database" in Supplement) from nasopharyngeal samples. These large databases were merged with the Human SwissProt database (20,361 protein sequences) and contaminant sequences database (116 protein sequences) to generate a large database of protein sequences for further processing (26,269,124 protein sequences).…”
Section: Protein Sequences Database Generation For Microbial Peptide ...mentioning
confidence: 99%
“…Orbitrap Fusion™ Tribrid™ Mass Spectrometer (Thermo Scientific, USA) coupled to a nanoLC system (Thermo Scientific, USA) was used for PRM experiments [33]. The isolation generated above was imported in the instrument method for PRM and used further for data acquisition.…”
Section: Prm Data Acquisition and Analysismentioning
confidence: 99%